O movimento dialético: a dor e o sofrimento na Fenomenologia do Espírito - Schio, Sônia Maria (Revista Eletrônica Estudos Hegelianos, 2016)
Resumo: Em uma sociedade que valoriza o prazer, o conforto, a diversão, afirmar que há uma concepção na qual o espírito precisa realizar um esforço, e o faz dolorosamente, para superar a negatividade que o envolve é, no mínimo, estranha. O processo dialético, segundo Jean Wahl (Le malheur de la conscience dans la Philosophie de Hegel), comporta essas características. A outra possibilidade hermenêutica, referente à dialética, apregoa que o movimento ocorre pelo “desejo”. Nesse sentido, é interessante investigar se a consciência prescinde, na superação das contradições com as quais se depara, da experiência de um empenho “sofrido” ou “desejante”, permitindo-lhe prosseguir rumo ao Espírito Absoluto. Nessa perspectiva, três são os momentos capitais: o da ilusão da consciência; o da consciência infeliz; e o da “entrada” no mundo da cultura. Palavras-chave: Consciência, Dor, Sofrimento, Desejo, Movimento dialético. Abstract: In a society that values the pleasure, the comfort, the amusement, to affirm that there is a conception for overcome the negative in which the spirit needs to accomplish an effort that is made painfully is, in the minimum, surprised. According to Jean Wahl, one interpretation sustain that the dialectic process holds the mentioned painfully characteristic. Another possible interpretation, according to him, sustain that the engine of the dialectic movement be the desire. According to the last perspective, it is interesting to investigate both, under the speculative point of view, but also with relationship to its philosophical and social present time importance, if the conscience overcomes the negative toward the absolute spirit without the contradictions, being that either the desire or the sufferance. Aiming to address this issue, three are the capital moments that must be presented: first the one of the illusion of the conscience and the obtaining of the sensitive certainty; second the dialect of the servant and master and the research of the unhappy conscience; third the one in which the self-awareness penetrates in the world of culture. Key-words: Conscience, Pain, Suffering, Desire, Dialectic movement.